1995
DOI: 10.1111/j.1651-2227.1995.tb13629.x
|View full text |Cite
|
Sign up to set email alerts
|

Normative developmental behavior with implications for health and health promotion among adolescents: a Swedish cross‐sectional survey

Abstract: I describe behavior with impact on health in adolescents against the background of characteristics of the Swedish society and analyse possible areas for improvement. A total of 4500 adolescents, aged 13-18 yr, in seven areas answered an anonymous questionnaire. Their socioeconomic backgrounds reflected mainstream adolescents. The response rate was 80-85%. Questions concerned health habits, exploratory behaviors regarding sexuality, use of alcohol and tobacco, problem behaviors, such as getting drunk, and life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 18 publications
1
36
0
1
Order By: Relevance
“…Comparisons can be made also with results from comprehensive Swedish surveys of normative developmental adolescent behaviour. 33 The analysis of clusters of problem behaviours, with related background factors, has been described as an instrument for identifying and helping troubled young people. 14 Early coitarche and reproductive health problems in young girls can preferably be analysed in the same manner.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons can be made also with results from comprehensive Swedish surveys of normative developmental adolescent behaviour. 33 The analysis of clusters of problem behaviours, with related background factors, has been described as an instrument for identifying and helping troubled young people. 14 Early coitarche and reproductive health problems in young girls can preferably be analysed in the same manner.…”
Section: Discussionmentioning
confidence: 99%
“…U ovom istraživanju je korišćen Upitnik samoprocjene (samoizvještavanja) o rizičnom ponašanju Q-2000 autora K. Berg-Kelly [21]. Upitnik rizičnog ponašanja Q-2000 sadrži 107 pitanja podijeljenih u dvanaest grupa.…”
Section: Metode Radaunclassified
“…Assessment of intake in the meal context is, for example, central for estimating the bio-availability of iron (Hallberg & Hulthen, 2000). Breakfast has been suggested to be a useful marker not only of dietary habits but also of other lifestyle factors (Berg-Kelly, 1995;Ruxton & Kirk, 1997;Höglund et al, 1998;Sjöberg et al, 2003a). In a recently published paper, we showed that meal pattern with omission of breakfast or breakfast and lunch was related to a clustering of less healthy lifestyle factors and food choice that might lead to a poorer nutrient intake (Sjöberg et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%